Mobile money innovations, income inequality and gender inclusion in sub-Saharan Africa - Simplice Asongu; Peter Agyemang-Mintah; Joseph Nnanna; Yolande E. Ngoungou (African Governance and Development Institute (AGDI), 2023)
The study assesses the role of mobile money innovations on income inequality and gender inclusion in 42 Sub-Saharan African countries for the period 1980 to 2019 using interactive quantile regressions. The following findings are established. First, income inequality unconditionally reduces the involvement of women in business and politics. Second, mobile money innovations interact with income inequality to have a positive impact on women in business and politics. Third, net effects from the role of mobile money innovations in income inequality for gender inclusion are consistently negative. Fourth, given that the positive conditional or interactive effects and negative net effects are consistent across the conditional distribution of gender inclusion, thresholds at which mobile money innovations can completely dampen the negative effect of income inequality on gender inclusion are provided. Among others, policy makers should work towards improving conditions for mobile money innovations. They should also be aware that reducing both income inequality and enhancing mobile money innovations simultaneously leads to more inclusive outcomes in terms of gender inclusion.
Keywords: G20; O40; I10; I20; I32; 330; Financial inclusion; inequality; mobile phones; sub-Saharan Africa; women